Before allyship: A model of integrating awareness of a privileged social identity - Bergkamp, Jude; Olson, Lindsay; Martin, Abi (Frontiers in Psychology, 2022)
Although the American Psychological Association encourages clinical psychologists to recognize and understand the experience of social privilege both within themselves and the individuals and communities they serve, there is a dearth of research in the field to guide this pursuit (APA, 2017). According to the available literature, an essential barrier to social privilege integration is its implicit and covert nature that prevents consistent consciousness due to hegemonic forces. This study explored the process, from initial social privilege awareness to the moment of the study, through individual interviews. A social-constructivist, grounded theory approach was utilized as it was aligned with the understudied phenomena oriented around social justice. The result is a developmental model of social privilege integration that explicates accumulated exposures to privilege, the resultant threat to and protection of personal identity, and the conducive factors that lead to reconciliation. Implications of this theoretical model include the importance of a developmental perspective to cultivate an understanding of individual prejudice attitudes and discriminatory behaviors, as well as a roadmap towards equitable change. This model may be used by clinical psychologists across multiple settings in response to the most recent APA multicultural guidelines.